Tirkah Distribution Obligation Rules According to Fiqh Al-Awlawiyyat - Muttaqin, Zainal; Zubir (State of Islamic Institute Langsa, 2023)
Fiqh al-awlawiyyat is the science of putting something in its position with the various standards (dhawabith al-awlawiyyat) used. Some of these standards are seen from various aspects such as the level of benefit, keeping mudharat away, and the efficiency of implementation time. This article is a literature research with a normative juridical approach. The methodology used is a descriptive study of analysis with primary sources in the form of literacy regarding fiqh al-awlawiyyat. The secondary source used is literacy that discusses fiqh and ushul al-fiqh which are relevant to the research variables. The results of the study concluded that the orderly distribution obligations of tirkah must have an orderly order, namely; the obligation of distribution of common property rights, the obligation of distribution of the cost of handling the remains, the obligation of distribution of the cost of repayment of mayit debts, the obligation of distribution of wills, and the obligation of distribution of inherited property.